"Todo ha sido a pulmón": Community organizing after disaster in Puerto Rico. Issue 3 (2nd October 2019) - Hayward, R. Anna; Morris, Zachary; Otero Ramos, Yamirelis; Silva Díaz, Alejandro
ABSTRACT: In this Notes from the Field, we highlight the work of community based organizations that filled essential gaps in the disaster recovery efforts in Puerto Rico for communities that were heavily damaged by Hurricane Maria yet received little formal government aid. We describe community mobilizing and organizing efforts and identify key lessons for eco-social work practice. As disaster risk increases with climate change, community led efforts are likely to prove vital for the effective protection of the most vulnerable population groups.